Penyuluhan Teknologi Pembenihan Ikan Bandeng Untuk Mendorong Kemandirian Produksi Benih Ikan Bandeng Di Kabupaten Bima Provinsi Nusa Tenggara Barat - Alis Mukhlis; Nadirah Karimatul Ilmi; Sanca Rahmatullah; Anita Prihatini Ilyas; Awan Dermawan (Universitas Mataram, 2020)
Milkfish (Chanos chanos Forskal) is one of the high economic value of brackish water fish and it has become the main commodity of brackish water fisheries for Bima Regency. Bima Bay was the center of milkfish production in Bima Regency with a pond area of around 1,612.16 Ha. Fishponds were spread in 3 (three) districts, namely Bolo sub-district covering 759.95 Ha, Woha sub-district covering 765.82 Ha, and Palibelo sub-district covering 86.39 Ha. As many as 11.41% of the total area of ponds used for milkfish enlargement throughout the year, while 88.59% used for milkfish enlargement and salt production alternately. The area of a pond was about 0.25-0.65 Ha using a stocking density of 4.000-6.000 milkfish fry/pond. The number of seeds needed for the Bima bay area was around 27.4 million per year. Even though milkfish hatchery technology has developed, the technology is not yet understood by milkfish farmers. Therefore, extension activities need to be carried out with the aim of increasing public understanding of seedling and quality of seedlings produced so that the independence of seed production in the future can be realized. Aquaculture Study Program of Vocational Program at Bima Regency of Mataram University conducted a counseling activity in Bima Regency in September 2019 with the theme is Milkfish Hatchery (Chanos chanos Forskal) Household Scale, Opportunities and Problems. It was attended by about 40 target communities, namely Milkfish Farmers in the Bima Bay area. Based on communication during counseling, there needs to be a demonstration plot for Milkfish Hatchery in Bima Regency as a place for training and learning related communities